(3GdJaSjQ GdcHjQs - (3GHf GdMLGe, GdHRGR, eMeO Hf GdYHGS Hf Ydj Hf eQhGf, cGf MjG (B328 (3g`s
(3ChdgG (B:s
... (3hbGd GNQL ef GdLfI Chd jhe ef Pj GdbYOI adeG cGf GdfGS ef Pj GdMLI CNQLg LHQGFjd Edi efi (B....s
(3BNQgG (B:s
... (3bGd fRdJ gPg GdBjI ajfG aj TjYJfG hPdc Cf Gddg SHMGfg jaVdfG hjaVd (B...s
(3JHUQI GdYfhGf (B:s
(3HBNQ GdfSNI HNW eZGjQ (B( (3JaSjQ GHf GdMLGe (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B/ (3dYeQ QVG cMGdg (B3/ 381s
(3eYLe GdeDdajf , dYeQ QVG cMGdg (B3/ 381s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs